Educación virtual en el desarrollo psicomotor en los estudiantes de la Escuela de Educación Básica “Gral. Juan Lavalle” - Quevedo Chato, Melany Lizeth (2022)
The research addressed “Virtual education in psychomotor development in the students from Basic Education School “Gral. Juan Lavalle”, to determine the impact of virtual education in psychomotor development in the students from Basic Education School “Gral. Juan Lavalle” Riobamba- Period 2021-2022. Virtual-education is a teaching method used by technological devices give ease of interaction between the teacher and the student. The work is presented as a cross-sectional study, with a qualitative and quantitative approach, corresponding to a non-experimental design with a descriptive methodology. In addition, it is bibliographic and field with a non-probabilistic and intentional sample consisting of 48 students and five teachers of the first year of Basic Education School "Gen. Juan Lavalle", the technique used is based on a survey to teachers and a psychometric test with the psychomotor development test instrument (TEPSI) directed to students. All statistical analyses to collect data were used in Excel application represented in tables and pies for their interpretation and discussion of the results. Among the results, it can be mentioned that virtual education has indirectly impacted the psychomotor development of children in the first year of General Basic Education, since it does not affect motor skills, language, and coordination.